Crystal structure of 3-acetyl-6-hydroxy-2H-chromen-2-one monohydrate, C11H10O5 - Xiong Zhi-Qiang; Yang Ling; Xiao Shu-Zhen; Yang Chen-Yu; Nie Xu-Liang (Zeitschrift für Kristallographie - New Crystal Structures)
[C11H10O5], monoclinic, P21/n, a = 7.041(3) Å, b = 9.339(4) Å, c = 15.614(6) Å, β = 103.03°, V = 1000.2(7) Å3, Z = 4, Rgt(F) = 0.0337, wRref(F2) = 0.0994, T = 296(2) K.